Plásmons em redes periódicas de nanofitas de grafeno e fosforeno - Miranda, José Orlando dos Santos (2023)
The modern plasmonics has gained renewed interest in the last decade with the advent of graphene synthesis in 2004 and, consequently, the emergence of new two-dimensional mate rials in the following years. It has become a viable tool for manipulating light with matter, possessing a range of attractive properties for new technological applications. Many potential applications of plasmonics in graphene are attributed to the fact that when doped, it supports surface plasmon-polaritons (SPPs)—electromagnetic waves coupled to the oscillations of free electrons plasma—propagating along the surface of a conductor. SPPs cannot be excited by direct light incidence in a homogeneous system due to the surface polariton’s momentum being much larger than that of incident light at the same frequency. Another lamellar material that has drawn considerable attention from the scientific community, due to its anisotropic properties and being a semiconductor with an adjustable energy gap concerning the number of layers or application of an external electric field, is phosphorene. As a consequence of its anisotropic band structure, leading to a strong angular dependence on incident light absorption, it has been shown that the dispersion of plasmons in phosphorene exhibits direction-dependent behaviors. Some mechanisms for promoting SPP excitation involve the use of Bragg diffraction gratings or periodic surface ripple on the conductor. Similarly, in graphene, recent studies have investigated electromagnetic radiation scattering by metallic grating patterns on top of graphene as an alter native method to excite SPP. Additionally, it has recently been demonstrated that modulating optical conductivity efficiently leads to electromagnetic radiation coupling with SPPs in graphene without the need for a grating. In this context, the present work investigates the scattering of electromagnetic radiation incident on a two-dimensional system with periodically modulated conductivity deposited on a dielectric substrate. We analyze the radiation coupling with SPPs in the form of Bloch surface waves for the specific case of a periodic array of graphene nanoribbons and phosphorene, solving the scattering problem and calculating the transmittance, reflectance, and absorbance of plane waves incident on the system.